The ability of quantitative literacy of pre-service biology students - Ardiansyah, Ryan; Diella, Dea (Jurnal Pendidikan Biologi Indonesia, 2017)
This research have purpose to know and describe quantitative literacy of pre-service biology students based on six indicators of quantitative literacy. Methods used is descriptive with study survey. This research carried out at Siliwangi University with the subject as many as 30 pre-service biology students who take plant anatomy course. Based on the analysis of test and interview obtained that of 30 students, 4 students (13.3%) in high category, 10 students (33.3%) in medium category, and 16 students (53.3%) in low category. Overall, indicator of interpretation have succeeded owned by students, but other five indicators have not been owned. Lack of quantitative literacy of pre-service biology students is caused by course characteristics that tends to qualitative teaching materials that is not based on quantitative literacy, and inadequate facility to gain and analyzed quantitative data.